Masnun Tahir’s Nationalist Fiqh: The Integration of Islam and Nationalism in Addressing Social Challenges in Indonesia - Karimullah, Suud Sarim; Sugitanata, Arif (ADDIN, 2024)
This study analyzes Masnun Tahir’s thoughts on Nationalist fiqh as a solution to the challenges of pluralism, intolerance, and radicalism in Indonesia. Masnun Tahir proposes a paradigm of Nationalist fiqh that integrates Islamic values with the multicultural context of Indonesian nationhood. The study employs Jurgen Habermas’s Critical Hermeneutics theory as an analytical framework to explore the transformative dimensions of this thought, encompassing interfaith dialogue, education, and the strategic role of religious scholars (ulama) in fostering social harmony. Using a library research methodology and textual analysis, this research examines Masnun Tahir’s works and the relevance of his ideas in the social context. The findings indicate that Masnun Tahir’s Nationalist fiqh offers a comprehensive approach that balances Islamic teachings with national values, positioning pluralism as a strength to enhance unity. This paradigm encourages the application of contextual Islamic law that respects local values and aligns with societal needs. Interfaith dialogue emerges as a central pillar of this paradigm, functioning as a tool to strengthen social integration and minimize conflicts arising from differences in belief. Education based on Nationalist fiqh is also identified as a key element in shaping a tolerant and patriotic generation. The analysis reveals that the paradigm of Nationalist fiqh is not merely normative but also transformative, providing practical solutions to the challenges of intolerance and radicalism. However, its implementation faces obstacles, including social resistance and the need for cross-sectoral support. With inclusive and sustainable strategies, Nationalist fiqh holds significant potential as an instrument for inclusive social transformation in Indonesia. This study contributes to the enrichment of theoretical discourse and offers a new perspective on bridging religion and nationhood in the Indonesian context.